Mapping strategic management research - Thomas, Howard (Institutional Knowledge at Singapore Management University, 1984)
The term 'strategic management' is of relatively recent origin and is currently the accepted term for the fields of business policy and planing. However, as a separate field of study, it is still at a fairly young and relatively evolutionary stage. As a result, many definitions of strategy abound and terms 'strategic planning,' 'policy' and 'strategic management' often mean precisely the same thing to different authors. It is useful to cast the strategic management process as involving elements of a complex inquiry system based upon the examination of alternative perspectives and a simulation of entrepreneurial activity through institutionalizing the strategy-making process.